Life in the Balance: Are Women's Possible Selves Constrained by Men's Domestic Involvement?. (May 2019) - Croft, Alyssa; Schmader, Toni; Block, Katharina
Do young women's expectations about potential romantic partners' likelihood of adopting caregiving roles in the future contribute to whether they imagine themselves in nontraditional future roles? Meta-analyzed effect sizes of five experiments (total N = 645) supported this complementarity hypothesis . Women who were primed with family-focused (vs. career-focused) male exemplars (Preliminary Study) or information that men are rapidly (vs. slowly) assuming greater caregiving responsibilities (Studies 1-4) were more likely to envision becoming the primary economic provider and less likely to envision becoming the primary caregiver of their future families. A meta-analysis across studies revealed that gender role complementarity has a small-to-medium effect on both women's abstract expectations of becoming the primary economic provider ( d = .27) and the primary caregiver ( d = −.26). These patterns suggest that women's stereotypes about men's stagnant or changing gender roles might subtly constrain women's own expected work and family roles.